Fatal Gastrointestinal Hemorrhage in a Young Boy with Newly Diagnosed Metastatic Medulloblastoma on High Dose Dexamethasone - Victor Wong; Nathalie Lefloch; John R. Crawford (Hindawi Limited, 2014)
A 10-year-old boy with newly diagnosed metastatic medulloblastoma was placed on high dose dexamethasone and ranitidine prior to surgery. The child underwent subtotal resection and was discharged 5 days postoperatively with an uneventful hospital course on a tapering dose of dexamethasone and ranitidine. Over the next 2 days the patient complained of mild abdominal distension with flatulence, without pain, vomiting, or dysmotility. On follow-up in clinic 5 days after discharge, he had normal vital signs when he suddenly became pale and had loss of consciousness. Emergent computerized tomography of the head showed no acute hemorrhage and complete blood count revealed hemoglobin of 4.2 gm/dL. In spite of maximum resuscitation with copious blood products the patient died. Autopsy revealed evidence of duodenal perforation with intraluminal hemorrhage. This case demonstrates a rare fatal complication of high dose dexamethasone therapy even with concurrent gastrointestinal prophylactic therapy. We provide a review of the limited literature on steroid use in pediatric neurooncology with regard to gastrointestinal bleeding.